The effect of solid waste management investments in the Republic of Serbia - Pavlović, Aleksandra; Ivanišević, Andrea; Katić, Ivana; Lošonc, Alpar; Radišić, Mladen (Anali Ekonomskog fakulteta u Subotici, 2021)
The problem of establishing an effective solid waste management system is complex and still unresolved in Serbian municipalities, cities and settlements. Most landfills in Serbia do not meet basic sanitary standards and can often contain waste that is dangerous to human, plant and animal health, and waste that can be recycled is often dumped. The aim of this paper is to investigate the relationship between waste generation and private investments in waste management. Statistical method of multiple linear regression was used to examine the impact of three predictors – economic development, investments in waste management, and urban population, on the dependent variable – municipal solid waste generation. The results of the research reveal that investments in waste management in Serbia do not have an effect on the waste reduction because the financial resources for such investments are not adequately managed. There is a large number of scientific researches that have dealt with the analysis of the mentioned relationship, however, their number on the example of Serbia is rather scarce. The results of the research could be useful to the state administrations of the Republic of Serbia.